SOME INSIGHTS OF NEOLIBERALISM IN BRAZIL FROM A GLOBAL PERSPECTIVE - Limonad, Ester (Mercator, 2021)
Aiming to raise the debate and new interpretations, we rehearse a reflection to understand different, apparently, unrelated processes through an articulating effort of current issues, whose theoretical formulation and empirical apprehension still generate confusion. To underline that Brazil is not a particular case, we make some critical remarks on the neoliberalization of life and the social production of space. (a) To clarify the financialization mechanisms, (b) highlight some interactions among financial capital actions, backed by the State, the media, and right-wing political movements, and (c) underline how the persistence of patrimonialism and unconcluded modernity intensify such processes. Events unfolding around the world, changes in the Brazilian political and economic conjuncture, since late 2015, suggest the imperative to consider: a) the character of the capitalist State in the current phase of financialization and accumulation; b) the very meaning of neoliberalism; c) the association of financial capital and the State; d) the societal and sociability crisis established, given the dehumanization of the Other and the potential of financialization transform all elements and aspects of life and social space into financial assets. Keywords : Neoliberalizing Space; Capitalist State; Global South; Brazil; Sociability Crisis; Neocolonialism.